Preparation method of high-concentration flaky durene
By combining modified 13X molecular sieve with ultrasonic vibration, the problems of high energy consumption during high-temperature calcination regeneration and uneven crystal thickness were solved, achieving low-energy and high-efficiency preparation of high-concentration flake-shaped mesitylene, thus improving product purity and the effectiveness of subsequent processes.
Patent Information
- Application Number
- CN202511516097.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2025-11-21
AI Technical Summary
In the existing technology, the high-temperature calcination regeneration of 13X molecular sieve consumes a lot of energy and the adsorption capacity decreases after regeneration. The thickness of the flake-shaped pyromellitic dianhydride produced by the traditional preparation process is uneven, which easily leads to crystal agglomeration and affects the purity of pyromellitic dianhydride.
High-concentration flake-shaped mesitylene was prepared by using modified 13X molecular sieve, which was modified by mixing with lanthanum nitrate solution to reduce the regeneration temperature of the adsorbent, and by controlling crystal growth with ultrasonic vibration.
This method enables the efficient use of low-temperature regenerated adsorbents, improves the purity and yield of flake-shaped mesitylene, reduces energy consumption, and controls crystal thickness, which is beneficial for high-purity and efficient production in subsequent processes.
Smart Images

Figure CN120987723A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic compound preparation technology, specifically a method for preparing high-concentration flake-shaped mesitylene. Background Technology
[0002] Mesitylene, also known as 1,2,4,5-tetramethylbenzene, is an organic compound with the chemical formula C63-12 ... 10 H 14 It is mainly used in organic synthesis, and can also be used as a plasticizer and a raw material for the preparation of pyromellitic dianhydride and pyromellitic acid. Pyromellitic dianhydride is the core raw material for the synthesis of polyimide. Therefore, the purity and crystal morphology of pyromellitic dianhydride directly determine the insulation and high temperature resistance of the polyimide prepared subsequently.
[0003] In existing technologies, the production process of mesitylene typically involves C10 aromatics fraction separation, but this technology has the following problems: 1. Adsorbent regeneration issue: C10 aromatic fraction separation uses 13X molecular sieves for impurity adsorption. However, 13X molecular sieves need to undergo high-temperature calcination activation treatment before use to remove moisture, carbon dioxide, hydrogen sulfide and other gaseous impurities from the environment during storage and transportation, ensuring their adsorption and impurity removal performance. However, the 500-600℃ high-temperature calcination regeneration of 13X molecular sieves is energy-intensive, and the adsorption capacity will decrease after regeneration. 2. Crystal thickness issue: The thickness deviation of the flake-shaped pyromellitic dianhydride produced by the traditional preparation process exceeds 0.1 mm. In the subsequent preparation of pyromellitic dianhydride, crystal agglomeration is prone to occur, which affects the purity of the obtained pyromellitic dianhydride. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing high-concentration flake-shaped mesitylene to solve the problems mentioned in the background art.
[0005] A method for preparing high-concentration flake-shaped mesitylene, the specific steps of which are as follows: S1, Preparation of modified adsorbent, Mix 13X molecular sieve and lanthanum nitrate solution at a mass ratio of 1:(5-8) and stir for 1-2 hours. Then filter out the 13X molecular sieve and dry it to obtain modified 13X molecular sieve. S2. Raw material impurity removal Take 15-20% of the C10 aromatic fraction (by mass of mesitylene) and the modified 13X molecular sieve at a mass ratio of (8-12):1, add the mixture to the adsorption vessel, stir and adsorb for 1-2 hours, filter to obtain filtrate and filter residue, the filtrate is the pretreatment raw material, and the mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is ≤0.3%; S3, Modified adsorbent regeneration. Nitrogen gas at 120-150℃ is introduced into the filter residue at a flow rate of 0.5-1L / min for 2-3 hours to complete the regeneration of the modified 13X molecular sieve. S4, Dissolution and crystallization, The pretreated raw material and the composite solvent were placed in a crystallization vessel at a mass ratio of 1:(2-4). The temperature was first raised to 60-70℃ and held for 30-40 minutes until completely dissolved. During the holding process, the mixture was continuously stirred at a stirring rate of 200-250 rpm. After complete dissolution, the temperature was lowered to 10-15℃ at a rate of 5-8℃ / h. During the entire cooling process, 20-40kHz ultrasound was continuously applied, and the stirring rate was simultaneously reduced to 100-150 rpm. After cooling was completed, the ultrasound and stirring were turned off, and the mixture was held at 10-15℃ for 1-2 hours to obtain the crystallized liquid. The composite solvent is prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:(3-5):1; S5. Separation and drying. The crystallization solution is centrifuged to separate the crystals, and then the crystals are vacuum dried for 2-3 hours to obtain high-concentration flake-shaped mesitylene.
[0006] As a preferred embodiment of the above technical solution, the preparation method of the modified 13X molecular sieve in S1 is as follows: Take 13X molecular sieve with a particle size of 0.5-1 mm and 0.5-1 mol / L lanthanum nitrate solution and mix them at a mass ratio of 1:(5-8). Stir at 60-80℃ for 1-2 h. Then filter out the 13X molecular sieve and dry it at 120-150℃ for 3-5 h to obtain modified 13X molecular sieve.
[0007] Furthermore, the specific preparation method of the modified 13X molecular sieve described in S1 is as follows: 13X molecular sieve with a particle size of 0.8 mm and 0.8 mol / L lanthanum nitrate solution were mixed at a mass ratio of 1:6 and stirred at 70 °C for 1.5 h. The 13X molecular sieve was then filtered out and dried at 130 °C for 4 h to obtain modified 13X molecular sieve.
[0008] As a preferred embodiment of the above technical solution, the preparation method of the pretreated raw material in S2 is as follows: Take 15-20% of the C10 aromatic fraction of mesitylene by mass and mix it with the modified 13X molecular sieve at a mass ratio of (8-12):1. Add the mixture to the adsorption vessel and stir at 20-40℃ and 100-150rpm for 1-2 hours. Filter to obtain filtrate and filter residue. The filtrate is the pretreatment raw material. The mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is ≤0.3%.
[0009] Furthermore, the specific method for preparing the pretreated raw materials described in S2 is as follows: A C10 aromatic fraction with a mass ratio of 18% of mesitylene and the modified 13X molecular sieve were mixed at a mass ratio of 8:1 and added to an adsorption vessel. The mixture was stirred and adsorbed at 30°C and a stirring rate of 120 rpm for 1.5 h. The mixture was then filtered to obtain a filtrate and a filter residue. The filtrate was used as the pretreatment raw material. The mass ratio of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material was ≤0.3%.
[0010] As a preferred embodiment of the above technical solution, the composite solvent is prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:4:1.
[0011] As a preferred embodiment of the above technical solution, nitrogen gas at 150°C is introduced into the filter residue at a flow rate of 1L / min for 2 hours to complete the regeneration of the modified 13X molecular sieve.
[0012] As a preferred embodiment of the above technical solution, the pretreated raw material and the composite solvent are placed in a crystallization vessel at a mass ratio of 1:3. The temperature is first raised to 65°C and held for 35 minutes until completely dissolved. During the holding process, the mixture is continuously stirred at a stirring rate of 220 rpm. After complete dissolution, the temperature is lowered to 12°C at a rate of 6°C / h. Throughout the cooling process, 30 kHz ultrasound is continuously applied, and the stirring rate is simultaneously reduced to 120 rpm. After cooling is completed, the ultrasound and stirring are turned off, and the mixture is held at 12°C for 1.5 hours to obtain the crystallized liquid.
[0013] As a preferred embodiment of the above technical solution, the crystallizing liquid is centrifuged to separate the crystals, and then the crystals are vacuum dried for 2.5 hours to obtain high-concentration flake-shaped mesitylene.
[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. La reaction of 13X molecular sieve 3+ Modification treatment, La 3+ Load 2-3%, La 3+ It can enhance the coordination adsorption capacity of molecular sieves for heavy component impurities such as naphthalene and dimethylnaphthalene, and reduce the binding capacity between the adsorbate and the molecular sieve channels, thus achieving low-temperature regeneration.
[0015] 2. Impurities in polycyclic aromatic hydrocarbon molecules such as naphthalene and dimethylnaphthalene contain conjugated fused ring structures, due to La 3+ The empty orbitals can combine with the π-electron cloud of fused rings, therefore impurities in polycyclic aromatic hydrocarbon molecules can combine with La. 3+ They form strong coordination bonds, and their molecular size matches the pore size of the modified 13X molecular sieve, making them easily trapped by the pores of the modified 13X molecular sieve; while monocyclic aromatic hydrocarbons such as p-tetramethylbenzene and diethylbenzene contain only one benzene ring, have low π electron cloud density, and are more susceptible to La2+ ionization. 3+Its coordination effect is extremely weak; and its molecular polarity is much lower than that of polycyclic aromatic hydrocarbons, so it cannot be strongly adsorbed by the polar sites in the molecular sieve channels. Therefore, it is hardly retained during the adsorption process at 20-40℃.
[0016] Monocyclic aromatic hydrocarbons that are not selectively removed by modified 13X molecular sieves can be separated and converted through subsequent processes, which not only does not affect the purity and morphology of mesitylene, but also improves the overall utilization rate of raw materials.
[0017] 3. Ultrasonic vibration can break up tiny crystal nuclei in supersaturated solutions, preventing excessive local crystal growth, while promoting the orderly arrangement of solvent molecules and guiding crystals to grow into regular sheets along specific directions. Attached Figure Description
[0018] Figure 1 This is a chromatogram for detecting the purity of flaky mesitylene crystals in Example 3 of the present invention. Detailed Implementation
[0019] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention.
[0020] A method for preparing high-concentration flake-shaped mesitylene, the specific steps of which are as follows: S1, Preparation of modified adsorbent, Take 13X molecular sieve with a particle size of 0.5-1 mm and 0.5-1 mol / L lanthanum nitrate solution and mix them at a mass ratio of 1:(5-8). Stir at 60-80℃ for 1-2 h. Then filter out the 13X molecular sieve and dry it at 120-150℃ for 3-5 h to obtain modified 13X molecular sieve. In specific implementation, La 3+ Loading amount 2-3%, specific surface area ≥750m² / g, La 3+ It can enhance the coordination adsorption capacity of molecular sieves for heavy component impurities such as naphthalene and dimethylnaphthalene, and reduce the binding capacity between the adsorbate and the molecular sieve channels, thus achieving low-temperature regeneration.
[0021] S2. Raw material impurity removal Take 15-20% of the mass of C10 aromatic fraction (meta-tetramethylbenzene) and modified 13X molecular sieve at a mass ratio of (8-12):1 and add them to the adsorption vessel. Stir and adsorb at 20-40℃ and 100-150 rpm for 1-2 hours. Filter to obtain filtrate and filter residue. The filtrate is the pretreatment raw material. The mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is ≤0.3%. In practice, the remaining components in the pretreated raw materials are monocyclic aromatic hydrocarbons that are naturally present in the C10 aromatic fraction and have not been selectively removed by the modified 13X molecular sieve. These monocyclic aromatic hydrocarbons can be separated and converted through subsequent processes, which not only does not affect the purity and form of mesitylene, but also improves the overall utilization rate of the raw materials.
[0022] It should be noted that polycyclic aromatic hydrocarbon impurities such as naphthalene and dimethylnaphthalene contain conjugated fused ring structures, due to La 3+ The empty orbitals can combine with the π-electron cloud of fused rings, therefore impurities in polycyclic aromatic hydrocarbon molecules can combine with La. 3+ It forms strong coordination bonds, and its molecular size matches the pore size of the modified 13X molecular sieve, making it easy to be trapped by the pore size of the modified 13X molecular sieve. Monocyclic aromatic hydrocarbons such as p-tetramethylbenzene and diethylbenzene contain only one benzene ring, have low π-electron cloud density, and are similar to La... 3+ Its coordination effect is extremely weak; and its molecular polarity is much lower than that of polycyclic aromatic hydrocarbons, so it cannot be strongly adsorbed by the polar sites in the molecular sieve channels. Therefore, it is hardly retained during the adsorption process at 20-40℃.
[0023] S3, Modified adsorbent regeneration. Nitrogen gas at 120-150℃ is introduced into the filter residue at a flow rate of 0.5-1L / min for 2-3 hours to complete the regeneration of the modified 13X molecular sieve. S4, Dissolution and crystallization, The pretreated raw materials and composite solvent were placed in a crystallization vessel at a mass ratio of 1:(2-4). The temperature was first raised to 60-70℃ and kept at that temperature for 30-40 minutes until completely dissolved. During the holding process, the mixture was continuously stirred at a stirring rate of 200-250 rpm. After complete dissolution, the temperature was lowered to 10-15℃ at a rate of 5-8℃ / h. During the entire cooling process, 20-40kHz ultrasound was continuously applied, and the stirring rate was simultaneously reduced to 100-150 rpm. After cooling was completed, the ultrasound and stirring were turned off, and the mixture was kept at 10-15℃ for 1-2 hours to obtain the crystallized liquid.
[0024] In practice, ultrasonic vibration can break up tiny crystal nuclei in a supersaturated solution, preventing excessive local crystal growth, while promoting the orderly arrangement of solvent molecules and guiding the crystal to grow into a regular sheet-like shape along a specific direction. Furthermore, the composite solvent is prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:(3-5):1.
[0025] S5. Separation and drying. The crystals are separated by centrifugation of the crystallization liquid, and then the crystals are vacuum dried for 2-3 hours to obtain high-concentration flake-shaped mesitylene.
[0026] Example 1 A method for preparing high-concentration flake-shaped mesitylene, the specific steps of which are as follows: S1, Preparation of modified adsorbent, 10 kg of 13X molecular sieve with a particle size of 0.5 mm was immersed in 50 kg of 0.5 mol / L lanthanum nitrate solution, stirred at 60 °C for 2 h, and then dried at 120 °C for 5 h to obtain La. 3+Modified 13X molecular sieve with a loading of 2%; S2. Raw material impurity removal Take 80 kg of C10 aromatic fraction (15% by mass of mesitylene and 2% by mass of polycyclic aromatic hydrocarbon impurities), add 10 kg of modified 13X molecular sieve, stir and adsorb at 20℃ and 100 rpm for 2 h, filter to obtain 78 kg of filtrate and 12 kg of filter residue. The filtrate is the pretreatment raw material, and the mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is reduced to 0.22%. S3, Modified adsorbent regeneration. Nitrogen gas at 120°C is introduced into the filter residue at a flow rate of 0.5 L / min for 3 hours to complete the regeneration of the modified 13X molecular sieve.
[0027] S4, Dissolution and crystallization, A composite solvent was prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:3:1.
[0028] 88 kg of pretreated raw material and 176 kg of composite solvent were placed in a crystallization vessel. The temperature was first raised to 60 °C and held for 30 min until completely dissolved. During the holding process, the mixture was continuously stirred at a stirring rate of 200 rpm. After complete dissolution, the temperature was lowered to 10 °C at a rate of 5 °C / h. During the entire cooling process, 20 kHz ultrasound was continuously applied, and the stirring rate was simultaneously reduced to 100 rpm. After cooling was completed, the ultrasound and stirring were turned off, and the mixture was held at 10 °C for 1 h to obtain the crystallized liquid.
[0029] S5. Separation and drying. The crystallization solution was centrifuged to separate the crystals, and then the crystals were vacuum dried for 2 hours to obtain 11.4 kg of flake-shaped mesitylene with a purity of 99.7%, a yield of 95.4%, and a thickness of 0.18 ± 0.03 mm.
[0030] Example 2 A method for preparing high-concentration flake-shaped mesitylene, the specific steps of which are as follows: S1, Preparation of modified adsorbent, 10 kg of 13X molecular sieve with a particle size of 1 mm was immersed in 80 kg of 0.5 mol / L lanthanum nitrate solution, stirred at 80 °C for 1 h, and then dried at 150 °C for 3 h to obtain La. 3+ Modified 13X molecular sieve with a loading of 2.5%; S2. Raw material impurity removal Take 80 kg of C10 aromatic fraction (20% by mass of mesitylene and 3% by mass of polycyclic aromatic hydrocarbon impurities), add 10 kg of modified 13X molecular sieve, stir and adsorb at 40℃ and 150 rpm for 1 h, filter to obtain 88 kg of filtrate and 2 kg of filter residue. The filtrate is the pretreatment raw material, and the mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is reduced to 0.3%. S3, Modified adsorbent regeneration. Nitrogen gas at 150°C was introduced into the filter residue at a flow rate of 1 L / min for 2 hours to complete the regeneration of the modified 13X molecular sieve.
[0031] S4, Dissolution and crystallization, A composite solvent was prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:5:1.
[0032] 88 kg of pretreated raw material and 352 kg of composite solvent were placed in a crystallization vessel. The temperature was first raised to 70 °C and held for 40 min until completely dissolved. During the holding process, the mixture was continuously stirred at a stirring rate of 250 rpm. After complete dissolution, the temperature was lowered to 15 °C at a rate of 8 °C / h. Throughout the cooling process, 40 kHz ultrasound was continuously applied, and the stirring rate was simultaneously reduced to 150 rpm. After cooling was completed, the ultrasound and stirring were turned off, and the mixture was held at 15 °C for 2 h to obtain the crystallized liquid.
[0033] S5. Separation and drying. The crystallization solution was centrifuged to separate the crystals, and then the crystals were vacuum dried for 3 hours to obtain 15.3 kg of flake-shaped mesitylene with a purity of 99.5%, a yield of 95.7%, and a thickness of 0.20 ± 0.02 mm.
[0034] Example 3 A method for preparing high-concentration flake-shaped mesitylene, the specific steps of which are as follows: S1, Preparation of modified adsorbent, 10 kg of 13X molecular sieve with a particle size of 0.8 mm was immersed in 60 kg of 0.8 mol / L lanthanum nitrate solution, stirred at 70 °C for 1.5 h, and then dried at 130 °C for 4 h to obtain La. 3+ Modified 13X molecular sieve with a loading of 3%; S2. Raw material impurity removal Take 80 kg of C10 aromatic fraction (18% by mass of mesitylene and 3% by mass of polycyclic aromatic hydrocarbon impurities), add 10 kg of modified 13X molecular sieve, stir and adsorb at 30℃ and 120 rpm for 1.5 h, filter to obtain 78 kg of filtrate and 12 kg of filter residue. The filtrate is the pretreatment raw material, and the mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is reduced to 0.24%. S3, Modified adsorbent regeneration. Nitrogen gas at 150°C was introduced into the filter residue at a flow rate of 1 L / min for 2 hours to complete the regeneration of the modified 13X molecular sieve.
[0035] S4, Dissolution and crystallization, A composite solvent was prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:5:1.
[0036] 88 kg of pretreated raw material and 264 kg of composite solvent were placed in a crystallization vessel. The temperature was first raised to 65°C and held for 35 min until completely dissolved. During the holding process, the mixture was continuously stirred at a stirring rate of 220 rpm. After complete dissolution, the temperature was lowered to 12°C at a rate of 6°C / h. During the entire cooling process, 30 kHz ultrasound was continuously applied, and the stirring rate was simultaneously reduced to 120 rpm. After cooling was completed, the ultrasound and stirring were turned off, and the mixture was held at 12°C for 1.5 h to obtain the crystallized liquid.
[0037] S5. Separation and drying. The crystallization solution was centrifuged to separate the crystals, and then the crystals were vacuum dried for 2.5 hours to obtain 14.0 kg of flake-shaped mesitylene with a purity of 99.6%, a yield of 97.2%, and a thickness of 0.16 ± 0.02 mm.
[0038] control group The difference between this control group and Example 3 is as follows: 1. The preparation methods of the modified adsorbent in S1 are different. 13X molecular sieve was activated by high-temperature calcination at 500-600℃ and then used as a modified adsorbent. 2. The regeneration methods for the modified adsorbent in S3 are different. 13X molecular sieve, after being activated by high-temperature calcination at 500-600℃, is used as a modified adsorbent. Its regeneration method is high-temperature calcination activation at 300-400℃.
[0039] Four adsorbents provided in the three examples and the control group were used to perform adsorption and impurity removal on C10 aromatic fractions. The mass percentage of polycyclic aromatic hydrocarbon impurities in the C10 aromatic fractions after impurity removal is shown in Table 1.
[0040] Table 1
[0041] As shown in Table 1, the modified 13X molecular sieve of the present invention can achieve the same adsorption and removal effect of polycyclic aromatic hydrocarbon impurities as the existing high-temperature calcination activated 13X molecular sieve, but the energy consumption is much lower than that of the existing high-temperature calcination activated 13X molecular sieve process.
[0042] Meanwhile, the present invention produces flake-shaped mesitylene with lower energy consumption, achieving the same crystal purity and yield as existing processes. Furthermore, the crystals are thinner, which is more conducive to the subsequent preparation of pyromellitic dianhydride.
[0043] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the modified 13X molecular sieve regenerated after operation S3 in Example 1 is used as an adsorbent in S2 of the method for preparing high-concentration flake-shaped mesitylene provided in Example 1, and is recycled 2, 4, 6, and 8 times.
[0044] Comparative Example 2 The only difference between Comparative Example 2 and Example 2 is that the modified 13X molecular sieve regenerated after operation S3 in Example 2 is used as an adsorbent in S2 of the high-concentration flake mesitylene preparation method provided in Example 2 for 2, 4, 6, and 8 cycles.
[0045] Comparative Example 3 The only difference between Comparative Example 3 and Example 3 is that the modified 13X molecular sieve regenerated after operation S3 in Example 3 is used as an adsorbent in S2 of the high-concentration flake-shaped mesitylene preparation method provided in Example 3 for 2, 4, 6, and 8 cycles.
[0046] Comparative Example 4 The only difference between Comparative Example 4 and the control group is that the modified adsorbent activated and regenerated by high-temperature calcination at 300-400℃ in the control group was recycled 2, 4, 6, and 8 times in S2 of the preparation method of high-concentration flake mesitylene provided by the control group.
[0047] The adsorption effects of the four adsorbents in the four comparative examples on polycyclic aromatic hydrocarbon impurities in the C10 aromatic hydrocarbon fraction were tested after 2, 4, 6 and 8 cycles of use. The results are shown in Table 2.
[0048] Table 2
[0049] As shown in Table 2, the modified 13X molecular sieve prepared by this invention, as an adsorbent for polycyclic aromatic hydrocarbon impurities, exhibits a relatively small decrease in adsorption capacity after multiple cycles. It can still maintain a good adsorption effect after 6 cycles, and the adsorption effect only weakens to a certain extent after 8 cycles.
[0050] However, when using 13X molecular sieve activated by traditional high-temperature calcination as an adsorbent for polycyclic aromatic hydrocarbon impurities, the adsorption capacity decreases significantly after 4 cycles, and almost completely loses its adsorption capacity after 8 cycles. Moreover, the 13X molecular sieve activated by high-temperature calcination needs to be reactivated by high-temperature calcination each time it is regenerated, which consumes a lot of energy.
[0051] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing high-concentration flake-shaped mesitylene, characterized in that, The specific steps are as follows: S1, Preparation of modified adsorbent, Mix 13X molecular sieve and lanthanum nitrate solution at a mass ratio of 1:(5-8) and stir for 1-2 hours. Then filter out the 13X molecular sieve and dry it to obtain modified 13X molecular sieve. S2. Raw material impurity removal Take 15-20% of the C10 aromatic fraction (by mass of mesitylene) and the modified 13X molecular sieve at a mass ratio of (8-12):1, add the mixture to the adsorption vessel, stir and adsorb for 1-2 hours, filter to obtain filtrate and filter residue, the filtrate is the pretreatment raw material, and the mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is ≤0.3%; S3, Modified adsorbent regeneration. Nitrogen gas at 120-150℃ is introduced into the filter residue at a flow rate of 0.5-1L / min for 2-3 hours to complete the regeneration of the modified 13X molecular sieve. S4, Dissolution and crystallization, The pretreated raw material and the composite solvent were placed in a crystallization vessel at a mass ratio of 1:(2-4). The temperature was first raised to 60-70℃ and held for 30-40 minutes until completely dissolved. During the holding process, the mixture was continuously stirred at a stirring rate of 200-250 rpm. After complete dissolution, the temperature was lowered to 10-15℃ at a rate of 5-8℃ / h. During the entire cooling process, 20-40kHz ultrasound was continuously applied, and the stirring rate was simultaneously reduced to 100-150 rpm. After cooling was completed, the ultrasound and stirring were turned off, and the mixture was held at 10-15℃ for 1-2 hours to obtain the crystallized liquid. The composite solvent is prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:(3-5):1; S5. Separation and drying. The crystallization solution is centrifuged to separate the crystals, and then the crystals are vacuum dried for 2-3 hours to obtain high-concentration flake-shaped mesitylene.
2. The method for preparing high-concentration flake-shaped mesitylene according to claim 1, characterized in that, The specific preparation method of the modified 13X molecular sieve described in S1 is as follows: Take 13X molecular sieve with a particle size of 0.5-1 mm and 0.5-1 mol / L lanthanum nitrate solution and mix them at a mass ratio of 1:(5-8). Stir at 60-80℃ for 1-2 h. Then filter out the 13X molecular sieve and dry it at 120-150℃ for 3-5 h to obtain modified 13X molecular sieve.
3. The method for preparing high-concentration flake-shaped mesitylene according to claim 1, characterized in that, The specific preparation method of the pretreated raw materials described in S2 is as follows: Take 15-20% of the C10 aromatic fraction of mesitylene by mass and mix it with the modified 13X molecular sieve at a mass ratio of (8-12):
1. Add the mixture to the adsorption vessel and stir at 20-40℃ and 100-150rpm for 1-2 hours. Filter to obtain filtrate and filter residue. The filtrate is the pretreatment raw material. The mass percentage of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material is ≤0.3%.
4. The method for preparing high-concentration flake-shaped mesitylene according to claim 1, characterized in that, The composite solvent is prepared by mixing anhydrous ethanol, ethyl acetate and N,N-dimethylformamide in a mass ratio of 5:4:
1.
5. The method for preparing high-concentration flake-shaped mesitylene according to claim 2, characterized in that, 13X molecular sieve with a particle size of 0.8 mm and 0.8 mol / L lanthanum nitrate solution were mixed at a mass ratio of 1:6 and stirred at 70 °C for 1.5 h. The 13X molecular sieve was then filtered out and dried at 130 °C for 4 h to obtain modified 13X molecular sieve.
6. The method for preparing high-concentration flake-shaped mesitylene according to claim 3, characterized in that, A C10 aromatic fraction with a mass ratio of 18% of mesitylene and the modified 13X molecular sieve were mixed at a mass ratio of 8:1 and added to an adsorption vessel. The mixture was stirred and adsorbed at 30°C and a stirring rate of 120 rpm for 1.5 h. The mixture was then filtered to obtain a filtrate and a filter residue. The filtrate was used as the pretreatment raw material. The mass ratio of polycyclic aromatic hydrocarbon impurities in the pretreatment raw material was ≤0.3%.
7. The method for preparing high-concentration flake-shaped mesitylene according to claim 1, characterized in that, Nitrogen gas at 150°C is introduced into the filter residue at a flow rate of 1 L / min for 2 hours to complete the regeneration of the modified 13X molecular sieve.
8. The method for preparing high-concentration flake-shaped mesitylene according to claim 1, characterized in that, The pretreated raw material and the composite solvent were placed in a crystallization vessel at a mass ratio of 1:
3. The temperature was first raised to 65°C and held for 35 minutes until completely dissolved. During the holding process, the mixture was continuously stirred at a stirring rate of 220 rpm. After complete dissolution, the temperature was lowered to 12°C at a rate of 6°C / h. During the entire cooling process, 30 kHz ultrasound was continuously applied, and the stirring rate was simultaneously reduced to 120 rpm. After cooling was completed, the ultrasound and stirring were turned off, and the mixture was held at 12°C for 1.5 hours to obtain the crystallized liquid.
9. The method for preparing high-concentration flake-shaped mesitylene according to claim 1, characterized in that, The crystallization solution was centrifuged to separate the crystals, and then the crystals were vacuum dried for 2.5 hours to obtain high-concentration flake-shaped mesitylene.
Citation Information
Patent Citations
Non-hydrogenation aromatization upgrading method for naphtha
CN101497816A
Preparation method of modified HZSM-5 molecular sieve catalyst for synthesizing 1,2,4,5-tetramethylbenzene and catalyst prepared by method
CN110280301A
Method for separating durene from durene enrichment liquid
CN115433051A
Process for separating durene from substituted benzene hydrocarbons
US5223589A